Challenges in traumatic spinal cord injury care in developing countries – a scoping review - Ranjbar Hameghavandi, Mohammad Hosein; Khodadoust, Elaheh; Hassan Zadeh Tabatabaei, Mahgol Sadat; Farahbakhsh, Farzin; Ghodsi, Zahra; Rostamkhani, Sabra; Ghashghaie, Shahryar; Abbaszade, Mahkame; Arbabi, Arash; Hossieni, Seyedeh Maede; Sadeghi-Naini, Mohsen; Atlasi, Rasha; et al. (Frontiers in Public Health, 2024)
Objective To evaluate the leading challenges in developing countries’ traumatic spinal cord injury (TSCI) care. Methods We conducted a systematic search in electronic databases of PubMed, SCOPUS, Web of Science, EMBASE, and Cochrane Library on 16 April 2023. Studies that investigated challenges associated with the management of TSCI in developing countries were eligible for review. We extracted related outcomes and categorized them into four distinct parts: injury prevention, pre-hospital care, in-hospital care, and post-hospital care. Results We identified 82 articles that met the eligibility criteria including 13 studies on injury prevention, 25 on pre-hospital care, 32 on in-hospital care, and 61 on post-hospital care. Challenges related to post-hospital problems including the personal, financial, and social consequences of patients’ disabilities and the deficiencies in empowering people with TSCI were foremost studied. Lack of trained human resources, insufficient public education and delays in care delivery were barriers in the acute and chronic management of TSCI. A well-defined pre-hospital network and standard guidelines for the management of acute neurotrauma are needed. Critical challenges in injury prevention include deficiencies in infrastructure and supportive legislation. Conclusion Studies focusing on injury prevention and pre-hospital care in TSCI management in developing countries warrant further investigation. It is imperative to develop systematic and evidence-based initiatives that are specifically tailored to the unique circumstances of each country to address these challenges effectively. By understanding the primary obstacles, policymakers and healthcare providers can establish goals for improving education, planning, legislation, and resource allocation.